Психологічна готовність студентів до розв’язання конфліктів - Березовська Лариса; Конц Тімеа; Larysa Berezovska; Konts Timea; Koncz Tímea (Вид-во МДУ, 2016)
Резюме. У статті розглядається психологічна готовність студентів до розв’язання професійних конфліктів. Розкрито психологічну готовність як на особистісному (передбачає вивчення готовності як комплексу інтегрованих, але різнорідних властивостей, що розрізняються за місцем і функціями в регуляції діяльності), так і на функціональному (виявлення процесуальних якостей, безпосередньо значимих для діяльності) рівнях. Представлено структуру готовності особистості до розв’язання конфліктів, що складається із мотиваційного, когнітивного, операційного, емоційного та комунікативного компонентів. Проаналізовано дані структурні складові.

Abstract. In this article, psychological readiness of students to the professional conflicts solving is considered. The object of the article is considering theoretical approaches to the psychological readiness of students to the conflicts solving. It is revealed the psychological readiness as on the personal (it anticipates study of the readiness as complex of the integrated, but mixed qualities, which differ by place and functions in the activity regulation), so on the functional (occurrence of the processual qualities, directly meaningful for activity) levels. It is represented the native scientists’ analysis of different approaches to the problems of psychological readiness to the conflicts solving, which is considered as the sustainable system of the professionally important personality qualities, as integrative personality quality, as psychological creation which determines features of the professional behavior and activity in the conflict situation, as the component of professional readiness, as the ability of the conflicts solving in the professional sphere. In addition, psychological readiness is considered as conflictological competence, which is connected as with the results of activity, so with the concrete activity – concrete problems solving. The readiness to the conflicts solving is considering as the integral psychological creation, which creates subjective preconditions of professional behavior and activity in the conflict situation. The structure of personality readiness to the conflict solving is represented, which is composed of motivational, cognitive, operating, emotional and communicative components. Structural components of the readiness are tightly intertwined and only together can provide successful conflicts solving. Representation of only one of the components essentially limits the opportunities to construct conflicts solving. Conducted analysis can become the foundation for studying components of psychological readiness of students to the professional conflict solving, and means, methods of warning, prevention and conflicts solving in the future professional activity.
Keywords: психологічна готовність; компонент; студенти; розв’язання; конфлікт